Membedah Faktor-faktor Penyebab Terjadinya Ikhtilaf di Kalangan Ulama - Muhammad Ikhsan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2016)
Dissimalarity opinion among the ulema, specially fuqaha, is a treasure in Islamic Study of Laws. The ability of Islamic laws in responds the challenges on every period is related to the existence of the basic ikhtilaf among the ulema. So that, discussions to bring back the dissimaliriy opinions among moslem on the right path must be followed by serious discussion on the ikhtilaf principles as practiced by the early generation of Islamic ummah. Keyword: Ikhtilāf, Mażhab, Fikih Islam.